(untitled) (Stylos, 2019)
In Euripides’ Hippolytus, the young man whose name serves as the tragedy title brags about his purity and chastity, as he refuses to accept Cypris’ gifts while adoring the goddess Artemis. He seems to have a special relationship with her which, sometimes, even amounts to an identification. This work will focus on analyzing different passages in which a parallelism between Hippolytus and a maiden (parthénos) is constructed, particularly within the prologue, the agon between Theseus and his son, and the exodus. Likewise, both his virginity and his closeness to Artemis allow us to relate him with Iphigenia —a sacrificial victim also murdered by her father. This feminization process will be considered as a condition of possibility of filicide, by understanding that the death of a male son caused by his father is a very serious and unusual event in classical Greek culture.